Pulmonary barotrauma as a complication of mechanical ventilation for management of COVID-19 associated acute respiratory distress syndrome (CARDS) - Khan, Shahmeer; Kiran Hilal; Arshad, Ainan; Nankani, Avinash; Zehra Rizvi, Syeda Zoha; Ul Haq, Tanveer (Journal of the Pakistan Medical Association, 2023)
Objectives: To identify that incidence of pulmonary barotrauma secondary to mechanical ventilation for the management of acute respiratory distress syndrome associated with coronavirus-disease-2019, and to compare it with the incidence of pulmonary barotrauma trauma secondary to mechanical ventilation associated with all the other causes. Method: The retrospective case-control study was conducted at the Aga Khan University Hospital, Karachi, and comprised data from October 2020 to March 2021 of patients who underwent mechanical ventilation. The data was divided into two groups. Data of acute respiratory distress syndrome associated with coronavirus-disease-2019 was in group 1, and that of acute respiratory distress syndrome associated with any other cause in control group 2. Medical records were reviewed to obtain demographic and clinical data, while the institutional picture archiving and communication system was used to review radiological images. Data was analysed using SPSS 24. Results: Of the 261 cases, 115(44%) were in group 1; 87(75.6%) males and 28(24.3%) females. There were 146(56%) controls in group 2; 96(65.7%) males and 50(34.2%) females. There were 142(54.4%) subjects aged >60 years; 61(43%) in group 1 and 81(57%) in group 2. The incidence of pulmonary barotrauma in group 1 was 39(34%) and 8(5.5%) in group 2 (p<0.0001). Conclusion: Mechanical ventilation in the management of acute respiratory distress syndrome associated with coronavirus-disease-2019 was found to be associated with a significantly higher incidence of pulmonary barotrauma than acute respiratory distress syndrome associated with any other cause. Key Words: COVID-19, Respiratory distress syndrome, Barotrauma, Pulmonary ventilation, Mediastinal emphysema.